O oponente escatológico de Daniel e o Anticristo do Apocalipse Siríaco de Daniel - Silva José, Sara Daiane (2014)
The Syriac Apocalypse of Daniel (Syr Apoc Dan), a Christian apocalypse from the seventh century of Common Era, is clearly tributary to the canonical book of Daniel (Dn). In its turn, Dn provided the figure of an eschatological opponent who was re-signified in Christianity: the Antichrist. The cosmic dimensions of the malevolent character of oppressive tyrant of Dn - his arrogance against the gods, the abomination of desolation, military conquests and persecutions of the saints, the change of the cosmic order, the time of the reign and death of the tyrant - are considered in this work compared with the Antichrist of the Syr Apoc Dan